2014
DOI: 10.1093/ofid/ofu080
|View full text |Cite
|
Sign up to set email alerts
|

Hypermucoviscous Klebsiella Syndrome Without Liver Abscess in a Patient With Immunoglobulin G2 Immune Deficiency

Abstract: Background Hypermucoviscous Klebsiella pneumoniae (HMVKP) emerged as a cause of invasive infections in South-East (SE) Asia. It has become the most common cause of liver abscess in that region, and it is a significant causative organism in endogenous endophthalmitis and meningitis. During the past decade, cases of this uniquely virulent organism have been reported outside of SE Asia, with a propensity to affect individuals of SE Asian descent. Cases have been reported from North America including Canada.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although there are multiple case reports and case series of hvKP in the USA and Canada (Alsaedi et al, 2014;Fierer et al, 2011;Frazee et al, 2009;Keynan et al, 2007;Lederman & Crum, 2005a, b;McCabe et al, 2010;Nadasy et al, 2007;Pastagia & Arumugam, 2008;Patel et al, 2014;Pomakova et al, 2012), none of these studies reported the prevalence of hvKP. The only surveillance study in North America was from Alberta, Canada; an estimated prevalence of 8.2 % hvKP was found (Peirano et al, 2013).…”
mentioning
confidence: 99%
“…Although there are multiple case reports and case series of hvKP in the USA and Canada (Alsaedi et al, 2014;Fierer et al, 2011;Frazee et al, 2009;Keynan et al, 2007;Lederman & Crum, 2005a, b;McCabe et al, 2010;Nadasy et al, 2007;Pastagia & Arumugam, 2008;Patel et al, 2014;Pomakova et al, 2012), none of these studies reported the prevalence of hvKP. The only surveillance study in North America was from Alberta, Canada; an estimated prevalence of 8.2 % hvKP was found (Peirano et al, 2013).…”
mentioning
confidence: 99%
“…We also conducted a literature search of cases of meningitis sustained by hmKp/hvKp ( Table 3 and Table 4 ) using the PubMed Database (only articles in English were taken into account) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The following terms and keywords were used for searching: Klebsiella hypervirulent cerebrospinal fluid; Klebsiella hypermucoviscous meningitis; hypervirulent Klebsiella pneumoniae meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the classic HvKPS has liver abscesses, some cases have been described as an extrahepatic disease without liver abscesses, such as isolated muscle abscesses, necrotising fasciitis, osteomyelitis, septic arthritis, renal abscess, meningitis and prostate and bloodstream infections without abscesses 11–18. Further research is needed to unravel why some patients present with the typical phenotype while others do not.…”
Section: Discussionmentioning
confidence: 99%